2015
DOI: 10.1111/jsm.12823
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dysfunction in Veterans with Post-Traumatic Stress Disorder

Abstract: Introduction Veterans with post-traumatic stress disorder (PTSD) experience high rates of sexual dysfunction. However, the topic of sexual dysfunction is often overlooked clinically and underexamined in the PTSD research literature. Clinician assessment and treatment of sexual dysfunction are particularly important for Veterans, who are at increased risk of exposure to trauma. Aim Review the literature regarding sexual dysfun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 52 publications
1
18
0
3
Order By: Relevance
“…The prevalence literature examining sexual problems in the context of post‐traumatic stress disorder (PTSD) is scarcer, although nearly 45% of rape survivors have been found to experience PTSD 3 months later (Elklit & Christiansen, ). There is a small evidence base for war veterans with PTSD and erectile difficulties or sexual pain (Bentsen, Giraldi, Kristensen, & Andersen, ; Kotler et al ., ; Tran, Dunckel, & Teng, ), but these studies tend not to focus specifically on sexual trauma. One study found a moderating effect of PTSD on sexual problems (odds ratio of 2.3; Letourneau, Resnick, Kilpatrick, Saunders, & Best, ) and another found that people who experienced sexual trauma were four times more likely to report sexual problems compared with non‐sexual trauma (Haase, Boos, Schoenfeld, & Hoyer, ).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence literature examining sexual problems in the context of post‐traumatic stress disorder (PTSD) is scarcer, although nearly 45% of rape survivors have been found to experience PTSD 3 months later (Elklit & Christiansen, ). There is a small evidence base for war veterans with PTSD and erectile difficulties or sexual pain (Bentsen, Giraldi, Kristensen, & Andersen, ; Kotler et al ., ; Tran, Dunckel, & Teng, ), but these studies tend not to focus specifically on sexual trauma. One study found a moderating effect of PTSD on sexual problems (odds ratio of 2.3; Letourneau, Resnick, Kilpatrick, Saunders, & Best, ) and another found that people who experienced sexual trauma were four times more likely to report sexual problems compared with non‐sexual trauma (Haase, Boos, Schoenfeld, & Hoyer, ).…”
Section: Introductionmentioning
confidence: 99%
“…Female sexual function is complex and multifaceted, and trauma and mental health diagnoses, such as PTSD, incurred during deployment and combat exposure are closely associated with sexual dysfunction. 62,63…”
Section: Reproductive Planning and Contraceptionmentioning
confidence: 99%
“…Jedoch erscheinen auch negative Auswirkungen intrusiver Symptome nach anderen Arten von Traumatisierung auf die Sexualität plausibel, wie z.B. Ängste nach physischer Gewalterfahrung davor, dass bestimmte Körper-teile berührt werden, intrusiv beeinflusste Schmerzen nach einem traumatischen Verkehrsunfall oder nach Kriegserfahrungen [Tran et al, 2015]. Starke emotionale Reaktionen können zudem zu dissoziativen Zuständen führen [Schauer und Elbert, 2010], die dann wiederum die Angst vor Sexualität aufrechterhalten, unter anderem auch, weil keine korrigierenden Erfahrungen gemacht werden können oder keine Diskrimination zur Traumasituation vorgenommen werden kann [van Berlo und Ensink, 2000;Hansen et al, 2012].…”
Section: Phänomenologie Und Diagnostik Sexueller Dysfunktionenunclassified
“…Einige Therapieverfahren schließen dem Expositionsteil Interventionen an, die den Schwerpunkt haben, das «Leben zurückzugewin-nen» (z.B. DBT-PTSD [Bohus et al, 2013] [Tran et al, 2015;Büttner et al, 2014;Yehuda et al, 2015]. Dies wurde bislang vornehmlich im Bereich von nichtsexueller Traumatisierung festgestellt, wobei sich Studien vor allem zu sexuellen Dysfunktionen bei Kriegsveteranen finden lassen [Tran et al, 2015;Arbanas, 2010].…”
Section: Behandlung Sexueller Dysfunktionen Im Rahmen Der Ptbs-therapieunclassified
See 1 more Smart Citation